Strategi Perbankan Syariah dalam mengadopsi Teknologi Fintech untuk Pengembangan Produk Digital Berbasis Syariah - Agusty, rizal ubaidilbar (Maliki Interdisciplinary Journal, 2025)
Sharia banking in Indonesia continues to grow rapidly in line with the increasing public need for financial products that comply with sharia principles, such as the prohibition of usury, gharar and maysir. On the other hand, financial technology (fintech) has become a revolutionary force in the global financial industry, offering faster, more efficient and more accessible solutions. This research aims to identify fintech adoption strategies in sharia banking, as well as the challenges and opportunities that exist in this integration process. The research method was carried out through a literature review and analysis of the latest trends in the fintech and sharia banking sectors. The research results show that although fintech offers great opportunities in expanding access to sharia finance, challenges such as compliance with sharia principles and management readiness need to be addressed. In conclusion, effective adoption of fintech will increase the competitiveness of sharia banking, expand the range of services, and strengthen its position in the global market, as long as it is carried out with the right strategy and strengthening governance according to sharia principles